2005
DOI: 10.1049/el:20057320
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of 4H-SiC UV single photon counting avalanche photodiode

Abstract: The first 4H-SiC UV single photon counting avalanche photodiode has been designed, fabricated and characterised. Spectral quantum efficiency from 250 to 370 nm is presented. Single photon counting at room temperature is demonstrated for the first time and counting efficiency is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 5 publications
1
24
0
Order By: Relevance
“…SiC-based APDs have been demonstrated with high quantum efficiencies in the solar-blind wavelength range, and have been shown to have high gain and low dark currents [8]- [12] . Recently reported devices with dark current densities of 63 nA/cm 2 demonstrated a gain of more than 10,000 and also showed a very low noise equivalent power of 20 fW [13] .…”
Section: Solar-blind Geiger-mode Avalanche Photodiode Detector Arraysmentioning
confidence: 99%
“…SiC-based APDs have been demonstrated with high quantum efficiencies in the solar-blind wavelength range, and have been shown to have high gain and low dark currents [8]- [12] . Recently reported devices with dark current densities of 63 nA/cm 2 demonstrated a gain of more than 10,000 and also showed a very low noise equivalent power of 20 fW [13] .…”
Section: Solar-blind Geiger-mode Avalanche Photodiode Detector Arraysmentioning
confidence: 99%
“…Ultraviolet-enhanced Si photodetectors may be used in UV detection systems, but they have higher dark currents (nA) 16 . Wide-bandgap semiconductor p-i-n photodiodes with high avalanche gain and low dark current have been reported that employ SiC epitaxial layers grown on SiC substrates 17,18 . These devices are potentially not as attractive as GaN APDs for biodetection applications because SiC is an indirect gap semiconductor for which the quantum efficiency is optimized at shorter wavelengths (< 300 nm) than that of the bioflourescence of interest.…”
Section: High Gain Gan Avalanche Photodiodes On Gan Substratesmentioning
confidence: 99%
“…Small-size SiC avalanche photodiodes have been previously demonstrated with a high single photon detection efficiency [3][4][5][6] and high solar photon rejection ratio [7]. In this work we present results of the integration of avalanche photodiode arrays and photomultipliers with thin film stack optical filters.…”
Section: Introductionmentioning
confidence: 96%